Answer :
Answer:
[tex]W_{s} =6\\W_{t} =-36[/tex]
Step-by-step explanation:
u v
[tex]u(1, -9) = 3.......................v(1, -9) = 0[/tex]
[tex]us(1, -9) = 9....................vs(1, -9) = -6[/tex]
[tex]ut(1, -9) = 4.......................vt(1, -9) = 7[/tex]
[tex]Fu(3, 0) = -2.....................Fv(3, 0) = -4[/tex]
To find [tex]W_{s}[/tex]
Now we can apply the above expression
W(s, t) = F(u(s, t), v(s, t))
(1,-9)=((u(1, -9), v(1, -9)), (u(1, -9), v(1, -9))) · ((1, -9), (1, -9))
=([tex]F_{u}[/tex](3, 0), [tex]F_{v}[/tex](3, 0)) · (9, -6)
[tex]=(-2,-4).(9,-6)\\=(-18)+(24)\\=6[/tex]
To find [tex]W_{t}[/tex]:
(1,-9)=((u(1, -9), v(1, -9)), (u(1, -9), v(1, -9))) · ((1, -9), (1, -9))
= ([tex]F_{u}[/tex](3, 0), [tex]F_{v}[/tex](3, 0)) · (4, 7)
[tex]=(-2,-4).(4,7)\\=(-8)+(-28)\\=-36[/tex]